The Factors That Affecting Exclusive Breastfeeding In The Working Area Of Public Health Center Pabuaran, Serang District, 2020 - Ratu Rohima; Herman Sudirman; Yeny Sulistyowati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2022)
Health is one aspect of community life, quality of life, labor productivity, high morbidity and mortality rates in infants and children. Breastmilk (ASI) is the best food for babies, especially babies aged 0-6 months, whose function cannot be replaced by any food and drink. Breastfeeding is the fulfillment of the rights of every mother and child. The research used is a quantitative method with a